ASIMETRI INFORMASI DAN BUDGETARY SLACK (STUDI PADA PEMERINTAH KABUPATEN DOMPU) - Lukman Effendy (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2017)
This study aims to examine the effect of informationa asymetry towards budgetary slack at Dompu District Local Goverment. The population is all of structural officials at SKPD of Dompu Disctrict Local Goverment. The amount of sample is is 74 respondent, which is resulted by Tabachnick and Fidel (2007) approach. The data were obtained by spreading 74 questionnaires to 74 respondents. The data were analyzed using Partial Least Square Ver. 3.00, to know the influence Information Asymetry to Budgetary Slack. The results of this study indicate that information asymetry dont have a significant effect on Budgetary Slack.